Amazonian National Museum: an outstanding debt - Lebrún Aspíllaga, Ana María (2017)
The Amazonian National Museum was intended to be a public cultural space in the region and a reference spot for the knowledge and understanding of the Amazonia, the natural resources, geography, and cultural expressions specific to each Amazonian community, their history and cities. The museum promoted the research, conservation, education, exhibition and dissemination of tangible and intangible, natural and cultural heritage in their original context. It was designed as an institution of national level and international relevance. This cultural space was devoted to the great natural and cultural richness and diversity of the Peruvian Amazonia. The collection comprised archeological, historic, natural, ethnographic, artistic, photographic, documentary items, among others. All of them would be subject to preventive preservation measures, both organic and non-organic, and would be included in a preservation and restoration program for all kind of pieces. Another aspect of particular relevance was the generation of a strong bond with the educational institutions under an intercultural and pedagogical approach, so that the Museum could be a supporting resource for the teacher during the educational process. The programs should be structured and aligned with the curriculum design of the educational institution so as to facilitate formal learning, with the exhibition being the canal to reinforce or support the knowledge gained in class.